Dieta de Lycengraulis Olidus (Günther, 1874) (Pisces: Engraulidae) en el Río Uruguay Inferior - Ferriz, Ricardo A.; López, Guilhermo R. (Bioikos – Título não-corrente, 1998)
The dietary habits oflycengraulisolidus(Günther, 1874) inhabiting Uruguay river were investigated. Stomach content analyses established that it had on carnivourous diet. lts most important food organism are copepods, cladocerans and fishes. There was a progression from planktivorous diet in fish beelow 90 mm total lenght to a predominantly piscivoruos diet in fish above 91 mm.